2008
DOI: 10.1111/j.1464-410x.2008.07813.x
|View full text |Cite
|
Sign up to set email alerts
|

Nocturia and associated morbidity in a Danish population of men and women aged 60–80 years

Abstract: OBJECTIVE To evaluate the association between nocturia and medical diseases, medication, urinary incontinence (UI), recurrent cystitis, smoking, alcohol, parity, hysterectomy, pelvic organ prolapse surgery, UI surgery, and prostate surgery. SUBJECTS AND METHODS The previously validated questionnaire the Nocturia, Nocturnal Enuresis and Sleep‐interruption Questionnaire was sent to 2000 women and 2000 men aged 60, 65, 70, 75, and 80 years. The population was selected at random from The Danish Civil Registration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 50 publications
(78 reference statements)
5
59
2
1
Order By: Relevance
“…In addition, the lack of arginine vasopressin (AVP) secretion and renal AVP resistance induced by diabetes may play a crucial role (20,21). People with obesity (BMI of > 27 kg/m 2 ) had higher odds for suffering from nocturia, as compared to those without obesity, which was consistent with numerous epidemiological studies (5,7,8,15,17). The exact mechanism by which obesity causes nocturia is not known.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In addition, the lack of arginine vasopressin (AVP) secretion and renal AVP resistance induced by diabetes may play a crucial role (20,21). People with obesity (BMI of > 27 kg/m 2 ) had higher odds for suffering from nocturia, as compared to those without obesity, which was consistent with numerous epidemiological studies (5,7,8,15,17). The exact mechanism by which obesity causes nocturia is not known.…”
Section: Discussionsupporting
confidence: 62%
“…Some earlier epidemiologic studies reported signifi cant associations of heart disease with nocturia (7-9), while others did not (6,10,11,17). A recent study conducted by Chiu et al demonstrated that patients with chronic heart failure suffer from three or more episodes of nocturia as compared to the controls (26).…”
Section: Discussionmentioning
confidence: 99%
“…This lack of recognition is likely affected by the fact that nocturia is a common symptom among people ≥50 years old and is associated with a variety of clinical syndromes and diagnoses, including hypertension, diabetes, obesity, benign prostatic hyperplasia, and coronary artery disease. 13,14 Oztura et al reported that nocturia episodes were significantly more frequent among patients with sleep-related breathing disorders. 20 Chen et al have also reported that nocturia is an independent predictor of severe obstructive sleep apnea in patients with ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Nocturia is another multifactorial disorder that can be caused by hypertension, diabetes, heart failure, or sleeping disorders. 13,14 OSAS can be an underlying cause of nocturia, although it is infrequently recognized, even in the field of urology. However, waking to urinate is an easily noticed and quantitative variable.…”
Section: Introductionmentioning
confidence: 99%
“…3 As previously suggested, 19 the cause of nocturia among older men is most probably multifactorial, and this could explain the previously reported associations between frequent nocturia episodes and higher disease burden. 20,21 Additionally, previous…”
Section: Introductionmentioning
confidence: 96%